2009
DOI: 10.1186/1758-3284-1-34
|View full text |Cite
|
Sign up to set email alerts
|

Potential for Raman spectroscopy to provide cancer screening using a peripheral blood sample

Abstract: Cancer poses a massive health burden with incidence rates expected to double globally over the next decade. In the United Kingdom screening programmes exists for cervical, breast, and colorectal cancer. The ability to screen individuals for solid malignant tumours using only a peripheral blood sample would revolutionise cancer services and permit early diagnosis and intervention. Raman spectroscopy interrogates native biochemistry through the interaction of light with matter, producing a high definition bioche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 22 publications
4
35
0
Order By: Relevance
“…The potential of FTIR and Raman spectroscopy has been widely investigated for diagnostic purposes for cell and tissue analysis and the feasibility to use them for serum sensing has been suggested and applied to a wide range of body fluids [53] ranging from serum [54][55][56][57], tears [58] urine or saliva [59][60][61]. In both Infrared and Raman spectroscopic studies, to date the analysis has predominantly been performed on air dried drops of serum deposited on spectroscopically neutral substrates such as CaF 2 [62,63] .…”
Section: Biophotonicsmentioning
confidence: 99%
“…The potential of FTIR and Raman spectroscopy has been widely investigated for diagnostic purposes for cell and tissue analysis and the feasibility to use them for serum sensing has been suggested and applied to a wide range of body fluids [53] ranging from serum [54][55][56][57], tears [58] urine or saliva [59][60][61]. In both Infrared and Raman spectroscopic studies, to date the analysis has predominantly been performed on air dried drops of serum deposited on spectroscopically neutral substrates such as CaF 2 [62,63] .…”
Section: Biophotonicsmentioning
confidence: 99%
“…23 In addition to identification of subtle changes in tissue biochemistry associated with oral disease or cancer progression, Raman spectroscopy of biofluids can also be utilized to identify cancer-related chemical and molecular changes, and as such represents an additional avenue for real time, noninvasive differential cancer diagnosis. Studies utilizing biofluids including serum, 24 plasma, 25 urine 26 and saliva 27 have reported success in the diagnosis of lung cancer, 24 head and neck cancer 25 and colorectal cancer. 28 While promising, one major limitation posed by Raman spectroscopy is the inherent weakness of Raman signals, which are not sensitive enough to merit this technique with clinical value.…”
Section: Raman Spectroscopy In Cancer Diagnosticsmentioning
confidence: 98%
“…This leads to the assumption that if NR is to be used for the analysis of blood components such as malignancy specific proteins for CRC other than those associated with red blood cells (RBC) an enhancement mechanism has to be used or blood samples must have RBC removed in order to overcome this issue (Figure 3). For example, Harris et al [57] (2009) discussed the potential of peripheral blood samples analysed by NR to provide cancer screening in head and neck cancer. Using Raman spectroscopy and LDA analysis alone the study found this technique to have approximately 65% specificity and sensitivity for the discrimination of cancer in peripheral blood samples.…”
Section: Detection Of Crc In Blood Samplesmentioning
confidence: 99%